Вплив культурного чинника на динаміку європейської інтеграції - Ковальчук, Т.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Статья посвящена исследованию характера и интенсивности влияния культурного фактора на динамику европейской интеграции. На примере Европейского Союза рассмотрены роль и значение культурного фактора как одного из главных предпосылок формирования объединенной Европы, чувства единства среди европейцев и «союза среди народов Европы». The article is dedicated to the research of the character and intensity of the cultural factor 's influence on the dynamics of European integration. By the example of the European Union the role and value of the cultural factor as one of the main background of the United Europe formation and as a tool for forging a sense of cohesion among Europeans and «the Union among the peoples of Europe» are considered.